1992
DOI: 10.1111/j.1365-2141.1992.tb06405.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a mechanical factor of haemolysis in patients with positive IgG‐type direct antiglobulin test?

Abstract: In autoimmune haemolytic anaemia, the presence of antibodies on the erythrocyte membrane results in haemolysis through an immune process, but does it not alter the rheological properties of red blood cells (RBC), thus adding a mechanical factor to haemolysis? This study was designed to examine the rheological properties of erythrocytes sensitized with IgG-type antibodies. The study involved 20 patients with anaemia and positive direct antiglobulin test, including 12 with straightforward haemolysis, 10 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Acquired lesions of the red cell membrane following autoantibody to antigen interactions play a relevant role for erythrocyte clearance, as demonstrated by several studies (Delamarie et al, 1992;Ballas et al, 1984;Packman & Leddy, 1993). In view of the current knowledge of the red cell membrane asymmetry, lack of exposure of spectrin on cell surface and structure of autoantigens in AIHA, alterations induced by a direct interaction between autoantibodies and spectrin molecules are highly improbable (Lutz et al, 1987); hence, the variations of ratios between each densitometric area of the principal membrane proteins and that of total spectrin in our patients as compared to controls can be considered suitable to reveal possible acquired lesions of red cell membrane proteins.…”
Section: Discussionmentioning
confidence: 93%
“…Acquired lesions of the red cell membrane following autoantibody to antigen interactions play a relevant role for erythrocyte clearance, as demonstrated by several studies (Delamarie et al, 1992;Ballas et al, 1984;Packman & Leddy, 1993). In view of the current knowledge of the red cell membrane asymmetry, lack of exposure of spectrin on cell surface and structure of autoantigens in AIHA, alterations induced by a direct interaction between autoantibodies and spectrin molecules are highly improbable (Lutz et al, 1987); hence, the variations of ratios between each densitometric area of the principal membrane proteins and that of total spectrin in our patients as compared to controls can be considered suitable to reveal possible acquired lesions of red cell membrane proteins.…”
Section: Discussionmentioning
confidence: 93%
“…Detrimental effects related to the influence of mem brane-bound IgG (either true autoantibodies or immune complexes of associated IgG bound via the C R 1 receptor [24,25]) on RBC clearance are unknown, despite the high prevalence of a positive DAT during HIV infection; how ever, autoantibodies may act as mechanical factor in fluencing haemolysis [12]. Our results confirm the high prevalence of a positive DAT in these patients, but do not show a correlation between DAT positivity and proteoly sis index, thus making it unlikely that alterations on the RBC membrane in HIV-infected patients were induced by red-cell-bound IgG.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of autoantibod ies to erythrocytes (frequently reported in HIV infection) upon red blood cell (RBC) survival are poorly investi-adversely affect the maturation or survival of early erythroblasts [8], It has been shown that at least two of these conditions (splenomegaly and antibody coating of red cells) are associated with membrane architecture instabil ity in several red cell disorders [9][10][11][12], Recent reports have suggested that in vitro proteolysis of RBC mem brane proteins from some congenital or acquired red cell diseases could principally depend on alterations in mem brane architecture, induced in vivo during erythrocyte maturation or circulation. Consequently, the study of in vitro red cell membrane proteolysis could be used to eval uate possible damage to membrane stability by various injuries occurring during the red cell lifespan [13][14][15].…”
Section: Introductionmentioning
confidence: 99%